2022
DOI: 10.3390/su14138147
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Small Particulate Matter on Tourism and Related SMEs in Chiang Mai, Thailand

Abstract: In northern Thailand, the problem of small particulate matter arises every year, with the primary source being agricultural-weed burning and wildfire. The tourism industry is strongly impacted and has been in the spotlight for the past few years. Thus, this study aims to investigate the effect of small particulate matter on tourism and related SMEs in Chiang Mai, Thailand. The data were collected from 286 entrepreneurs in the tourism and related SMEs sectors. The data were analyzed using data mining and associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This would result in potentially adverse health outcomes for both the population living close to this road [69] and those traveling along footpaths [70]. In addition, this may cause the negative outcome of tourists ceasing to visit the cultural tourism route [12,71], which, in turn, affects the long-term success of car-free cultural tourism routes.…”
Section: Spatial Distribution Of Pm 1 In the Case Studiesmentioning
confidence: 99%
“…This would result in potentially adverse health outcomes for both the population living close to this road [69] and those traveling along footpaths [70]. In addition, this may cause the negative outcome of tourists ceasing to visit the cultural tourism route [12,71], which, in turn, affects the long-term success of car-free cultural tourism routes.…”
Section: Spatial Distribution Of Pm 1 In the Case Studiesmentioning
confidence: 99%
“…Not only does the direct threat of fire danger cause economic disruptions, smoke and small particulate matter can render air quality unhealthy, forcing people to remain inside and limiting physical activities when outdoors. Srinamphon, Chernbumroong, and Tippayawong [23] found that "financial factors (accommodation, travel agency business, and souvenir businesses) were severely affected due to lower revenues and higher business costs during the period . .…”
Section: Literature Reviewmentioning
confidence: 99%
“…As public health concerns continue to escalate in Chonburi due to the detrimental effects of air pollution, the findings from this study can inform evidence-based decision-making and support the development of targeted interventions. By understanding the long-term mechanisms of PM2.5 in the region, policymakers can design and implement measures to reduce pollution sources, improve air quality, and safeguard the health and well-being of the local population [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%